Immunoenhancement on DNA vaccine of polyprotein gene in infectious bursal disease virus by co-delivery with plasmid encoding chicken interleukin-18 - YU Xia-meng; SHOU Chun-bo; ZHANG Xiao-dong; XU Gen-liang; YU Lian (浙江大学学报. 农业与生命科学版, 2008)
To further evaluate the immunoenhancement of chicken interleukin-18 (IL-18), the polyprotein of infectious bursal disease virus (IBDV) was prepared to DNA vaccine, and the DNA vaccine was coadministrated with the eukaryotic expression plasmid encoding interleukin-18 (pCI-IL-18), then boosted after 2 weeks, and challenged with virulent IBDV 5 weeks later. It is observed that chicken IL-18 could significantly enhance the proliferation responses of T lymphocytes from spleen and B lymphocytes from bursa. Meanwhile, it can raise the neutralization antibody level and enhance the protection against virulent IBDV induced by DNA vaccine. The results indicate the strong enhancement of immune responses to IBDV DNA vaccine by co-administration with chicken IL-18 (200 µg) (P<0.05).